Sacred Text and Sacred Language: Interpretation of Some Theolinguistic Terms (Linguostylistic Studies, 2020)
The article considers some basic terminological units of theolinguistics, analyzes different approaches to their use. In the focus of the analysis are the issues of interpreting the term religious text and differentiating it from the terms fideistic text, spiritual text, sacred text, confessional text, holy text, etc. It remains an open question. Some scholars distinguish between religious and sacred texts from the standpoint of differentiation of their genres. Sacred texts can be interpreted in a narrow (sacred books, prayers and hymns that are part of the liturgical practice of a religion /the Bible, the Koran, the Torah, the Canon of the Liturgy, etc./) and a broad, figurative meanig (ideological works that society accepts axiomatically when political ideology prevails over religion, science and art /work of K. Marx, F. Engels, V. Lenin in the USSR/). The key question is how to consider the very concept of the sacred. We support those scientists, who interpret the concept in terms of broad understanding of sacredness, emphasizing that the language of the sacred sphere (sacred, holy language) includes not only the text of Revelation but also some folklore aspects, thus contrasting the language of the sacrum (sacred) with the language of the profanum (profane).The terms apostolic languages, prescient languages, prophetic languages, and epistles languages are absolute synonyms for the languages in which the apostles first uttered the Word of God and the foundations of Christian doctrine. The qualification of these languages as holied (sacred, cult) is controversial, as it causes terminological homonymy. It is also debatable to limit the use of these terms to Greek, Latin, Ancient Hebrew, and Old Slavonic languages. We consider sacred (sacred, cult) languages not only those in which the Word of God was first uttered but also those that later began to be used in conducting services and into which the Holy Scriptures were translated.
Keywords: theolinguistics; religious text; sacred text; sacred language; holy language; cultlanguage.